Effects of date of harvesting of Lablab forage on milk offtake, milk quality, and liveweight changes in Bunaji cows when fed as supplement - Agyemang, K.; Hailu, Z.; Makun-Lugard, H.J. (1996)
As part of a research effort to develop technologies for smallholder dairy systems in peri-urban areas in Sub-Saharan Africa, ILRI and collaborating national institutions have been testing feeding strategies based on forage legumes. Lablab purpureum is an introduced forage which is gaining acceptance in the farming systems as a dual purpose legume. However information on agronomic, storage and feeding characteristics to livestock is not available. The objective of the current study was to compare forage yield, nutrient content and feeding qualities of Lablab harvested at day 100, 114, 128 and 142 after planting. The resultant hay designated F1, F2, F3 and F4, respectively, were fed to 4 groups of 5 Bunaji lactating cows in an on-farm feeding trial over a 10-wk period at a rate of 10.5 kg/week per cow. Harvested dry matter yields were 2.14, 3.04, 2.59 and 1.80 ton/ha. Milk offtake from cows fed F1, F2, F3, and F4 averaged 6.6, 4.9, 5.4 and 4.8 l/wk (SE=1.94), respectively. Milkfat percent were 3.2, 3.5, 5.0, and 3.6 (SE0.75). Corresponding milkprotein percent were 3.2, 4.0, 3.3 and 3.6 (SE=0.46). Weekly liveweight gains in the cows were 1.5, 3.7, 2.1 and 4.2 kg (SE=2.94). Ranking the various feeds and animal responses on a linear scale (1 to 4) showed that harvesting at day 114 gave the overall most desirable benefit. The implications of this harvesting date on overall household labor calender are being studied.